A comparison of total inward leakage measured using sodium chloride (NaCl) and corn oil aerosol methods for air-purifying respirators. Issue 8 (3rd August 2018) - Rengasamy, Samy; Zhuang, Ziqing; Niezgoda, George; Walbert, Gary; Lawrence, Robert; Boutin, Brenda; Hudnall, Judith; Monaghan, William P.; Bergman, Michael; Miller, Colleen; Harris, James; Coffey, Christopher
Abstract: The International Organization for Standardization (ISO) standard 16900-1:2014 specifies the use of sodium chloride (NaCl) and corn oil aerosols, and sulfur hexafluoride gas for measuring total inward leakage (TIL). However, a comparison of TIL between different agents is lacking. The objective of this study was to measure and compare TIL for respirators using corn oil and NaCl aerosols. TIL was measured with 10 subjects donning two models of filtering facepiece respirators (FFRs) including FFP1, N95, P100, and elastomeric half-mask respirators (ERs) in NaCl and corn oil aerosol test chambers, using continuous sampling methods. After fit testing with a PortaCount (TSI, Inc., St. Paul, MN) using the Occupational Safety and Health Administration (OSHA) protocol, five subjects were tested in the NaCl chamber first and then in the corn oil chamber, while other subjects tested in the reverse order. TIL was measured as a ratio of mass-based aerosol concentrations in-mask to the test chamber, while the subjects performed ISO 16900-1-defined exercises. The concentration of NaCl aerosol was measured using two flame photometers, and corn oil aerosol was measured with one light scattering photometer. The same instruments were used to measure filter penetration in both chambers using a Plexiglas setup. The size distribution of aerosols was determined using a scanning mobility particle sizer and charge was measured with an electrometer. Filter efficiency was measured using an 8130 Automated Filter Tester (TSI). Results showed the geometric mean TIL for corn oil aerosol for one model each of all respirator categories, except P100, were significantly (p < 0.05) greater than for NaCl aerosol. Filter penetration in the two test chambers showed a trend similar to TIL. The count median diameter was ∼82 nm for NaCl and ∼200 nm for corn oil aerosols. The net positive charge for NaCl aerosol was relatively larger. Both fit factor and filter efficiency influence TIL measurement. Overall, TIL determination with aerosols of different size distributions and charges using different methodologies may produce dissimilar results.